(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article looks at how water affects pipes and how to stop metal from getting rusty and damaged by salt. Different types of inhibitors are used to keep equipment and pipelines working for a long time. Inhibitors used in recycling water supply systems in the oil and gas industry have to meet certain special rules. We need to make a chemical that stops metal from rusting and stops salt from building up in water systems at oil refineries.